(untitled) (Research, Society and Development, 2020)
Sugarcane is one of the crops that has been expanding more and more in Brazil, increasing its planted areas day after day and, consequently, its production of sugar and ethanol. This review aims to evaluate productivity and agronomic aspects resulting from production under localized irrigation. Independent researchers analyzed the databases; Science Direct and Scopus, without language restriction, for articles published between January 1990 and May 2018. We include articles with the following characteristics: (a) cane and/or Saccharum officinarum, sugarcane, (b) irrigation and/or water management, availability of sugarcane, availability of water for irrigation of sugarcane, cultivation with a larger irrigated area, increased productivity, coefficient of water requirement for cultivation (c) localized irrigation, cane drip irrigation and drip irrigation in sugar cane. Of the studies analyzed, 100% found beneficial effects of the use of localized irrigation on the productivity of sugarcane, some articles reported that the influence of the implantation cost is greater than in other systems, however, it was concluded that the localized irrigation it was superior in all the attributes analyzed in the present study as gain in the increase of the stem yield. Observing that the irrigation system was more productive in all comparisons.